Harry Potter and the chamber of secrets - "Rowling, J.K" (London. Bloomsbury, 1999)
Harry Potter is a wizard. He is in his second year at Hogwarts School of Witchcraft and Wizardry. Little does he know that this year will be as eventful as the last - even getting there is an adventure!
Keywords: English Fiction